Urban Rewilding and Fourth Nature: “Wild Berlin” - García Vázquez, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
"Urban rewilding" is an environmental policy which demands returning parts of the cities to nature. It is particularly applied in “Fourth Nature” areas, vacant zones due to functional obsolescence that, over time, have become biodiverse urban ecosystems. Currently, both concepts are framed within the regenerative urbanism holistic vision, that integrates nature and city. This article consists of two parts. The first one begins by developing the concepts of urban rewilding and Fourth Nature, linking the latter to the shrinking cities phenomenon, derived of the deindustrialization of the Western economy. It then analyses the enhancement and defence of Fourth Nature preservation, emphasizing the paradigm shift that this ecological understanding of the city represents for urban planning. The second part of the article is dedicated to “Wild Berlin”. Due to historical reasons, this city has been a pioneer in the implementation of rewilding policies in Fourth Nature areas. Two of them are used as case study: the Gleisdreieck wild park and the Tempelhofer Feld recreation area.